The classroom moral compass – participation, engagement and transgression in classroom interaction. Issue 3 (2nd September 2017) - Hazel, Spencer; Mortensen, Kristian
Abstract: This article explores the moral accountability of second language classroom participation, evidenced in sequential environments where participants display an orientation to some or other transgression in the engagement framework. Classroom participation is a sensitive issue which touches on what Garfinkel (1964, 225) has referred to as the moral order, constituted through the seen-but-unnoticed practices that pass as the natural order of things . A transgression of the particular way an engagement framework is organised is accountable, and although usually non-critical, it often results in the onward flow of the classroom activity to be momentarily suspended in order to address the transgression. When a classroom participant violates this 'normality', it not only attracts attention but can even invite moral and psychological evaluations, and may threaten the social status of the member responsible. Participants manage the tension for adhering to certain (negative) social categories by adopting mitigating strategies, for example by occasioning a jocular frame when attending to the transgression. Drawing attention to potentially sensitive issues points at the underlying moral order and at what is handled as normal, which in turn provides the analyst with a window on the practices into which participants have been socialised.